Effects of storage condition on the physicochemical characteristics of sunflower seed oil. Issue 72 (20th December 2019) - Xu, Wei; Yao, Juan; Yi, Yang; Wang, Hong-Xun; Wang, Li-Mei
Abstract : Sunflowerseed oil needs a low-temperature and dark condition to remain flavor by reducing the changes of 3-methyl-2, 5-furandione, hexanal and 2-heptenal. Abstract : The effects of storage condition on the physicochemical characteristics of sunflower seed oil (SSO) were investigated, to understand the required conditions and the typical indicators for its quality control. The changes of SSO in peroxide value (PV), acid value (AV), fatty acid (FA) composition, Fourier transform infrared (FTIR) spectrum and volatile compound (VC) during 11 month storage under seven different conditions, were analyzed. The PVs and AVs of the seven groups all increased with time, but the PVs fluctuated strongly during the last 4 months. The between-group differences in PV and AV indicated that light-exposure and high-temperature (≥40 °C) both accelerated the production and degradation of primary oxidation products of FA. However, the FA composition of SSO did not obviously change regardless of storage condition and time, as well as its FTIR characteristics. By contrast, its VC composition was significantly changed by light-exposure and high-temperature (≥55 °C). 3-Methyl-2, 5-furandione, acetic acid/1-phenylethyl ester, 2-pentyl-furan and limonene might be the main VCs related to the desirable flavor, in which 3-methyl-2, 5-furandione in all the groups showed a significantly decreased percentage of VC composition during storage. Light-exposure and high-temperature enhanced the accumulation of aldehydes, especially hexanal and ( E )-2-heptenal, which principally contributed to the undesirable flavor of SSO. 3-Methyl-2, 5-furandione, hexanal and ( E )-2-heptenal were proposed to be marker compounds for its quality control. A low-temperature and dark condition is necessary for SSO to remain a desirable flavor.